Intravascular ultrasound imaging of angiographically normal coronary arteries: a prospective study in vivo. Issue 6 (June 1994) - Ge, J.; Erbel, R.; Gerber, T.; Görge, G.; Koch, L.; Haude, M.; Meyer, J.
Abstract : Intravascular ultrasound imaging (IVUS) was performed to elucidate the discrepancy between clinical history and angiographic findings and to measure the diameter and area of the lumen of the normal left coronary artery in 55 patients who presented with chest pain but had normal coronary angiograms. The left coronary artery (LCA) was scanned with a 4.8F, 20 MHz mechanically rotated ultrasound catheter at 413 sites. Atherosclerotic lesions were identified at 72 (17%) sites in 25 patients. The mean (SD) (range) plaque area was 5.55 (3.56) mm2 (2-26 mm2) and it occupied 28.8 (9.6)% (13-70%) of the coronary cross sectional area. Calcification was detected at 24 (33%) atherosclerotic sites in nine patients. The correlation coefficients for the lumen dimensions measured at normal sites by IVUS and by angiography were r = 0.93 (SEE = 0.43) mm for lumen diameter and r = 0.89 (SEE = 4.27) mm2 for lumen area (both p < 0.001). 16 of the 30 patients in whom no atherosclerotic plaques were detected in the LCA lumen by IVUS had no risk factors of coronary artery disease. The cross sectional area of 90 consecutive images of left main coronary artery (LMCA), proximal left anterior descending coronary artery (proximal LAD), and mid LAD was measured in these 16 subjects. The mean (SEM) areas at end diastole were LMCA 17.33 (7.98) mm2; proximal LAD 13.56 (5.85) mm2; mid LAD 9.75 (4.67) mm2. During the cardiac cycle the cross sectional area changed by 10.2 (4.0)% in the LMCA, by 8.3 (4.7)% in the proximal LAD, and by 9.8 (4.0)% in the mid LAD. In 11 patients with plagues the change in cross sectional area in plague segments (5.8(3.1)%) was significantly lower than in the segments from patients without plagues (p < 0.001). Lumen area reached a maximum in early diastole rather than in late diastole. IVUS can imagine atherosclerotic lesions that are angiographically silent; it also provides detailed information about plague characteristics. The variation in coronary cross sectional area during the cardiac cycle should not be ignored during quantitative analysis. Maximum dimensions in normal segments are reached in early diastole. Further studies are needed to clarify the clinical significance of atherosclerosis detected by IVUS in patients presenting with chest pain but normal coronary angiography.